Impact of land-use change and soil erosion on cultural landscapes: the case of cultural paths and sites in Paphos district, Cyprus - Cuca, Branka; Agapiou, Athos (My University, 2018)
Soil loss has been long characterized as one of the main threats of climate change with possible impact to natural and cultural heritage (UNESCO report 2006). This study illustrates how applied geomatics integrating earth observation and geographical information systems (GIS) can be used to quantify this threat in an UNESCO protected archeological site as well as on cultural routes such as the ancient Hellenistic-Roman Road network. Both study sites are located in the western part of Cyprus, and specifically in Paphos district, which is an area with undergoing major pressure caused by soil erosion and soil loss. Multi-temporal earth observation methods were applied for identification, mapping and estimation of the possible soil loss caused by soil erosion in the period of the past 30 years. The soil loss was estimated using the Revised Universal Soil Loss Equation (RUSLE) model. Special attention was given to the land use/land cover factor (C) and its impact on the overall estimation of the soil loss. Cover factor represents the effect of soil-disturbing activities, plants, crop sequence and productivity level, soil cover, and subsurface bio-mass on soil erosion. Urban areas have a definite role in retarding the recharge process, leading to increased runoff and soil loss in the broader area. On the other hand, natural vegetation plays a predominant role in reducing water erosion. In specific, cover factor was estimated for the cultural routes, classified and observed in years 1987 and 2016 in the District of Paphos. The variance of the values between 2 years was then calculated in order to identify the areas under major pressure of soil erosion caused by the changes in land use and land cover. In addition, high-resolution optical data were analyzed in order estimate the multi-temporal changes in soil loss in the archeological site of Nea Paphos. The results shows that integrated earth observation and GIS can be used as a systematic tool for monitoring cultural heritage sites against natural threats such as soil loss.
Keywords: C-factor; Cultural landscapes; Earth observation; GIS; Land-use change; Landsat; RUSLE; Satellite remote sensing; Sentinel-2; Soil erosion